Co-Electrolysis with CFY-Stacks. (30th May 2017) - Megel, Stefan; Dosch, Christian; Rothe, Stefan; Folgner, Christoph; Trofimenko, Nikolai; Rost, Axel; Kusnezoff, Mihails; Reichelt, Erik; Jahn, Matthias; Michaelis, Alexander; Bienert, Christian; Brandner, Marco
Abstract : The efficient high temperature electrolysis of steam (H2 O) as well as steam and CO2 co-electrolysis is of interest for potential application in a renewable energy system. The development of power-to-product processes as well as necessary components are in focus of current research activities at IKTS. The main system component is a high temperature electrolyzer (SOEC). In collaboration with Plansee SE the robust CFY stack technology has been developed over last ten years. This stack technology can be applied for SOFC, SOEC and reversible operation (rSOC) and establishes a universal platform for different applications. Performance maps of a MK352 CFY stack in steam and co-electrolysis operation show a difference in electric power demand of less than 2 %. The output syngas can be directly adjusted to typical compositions used for reactions like Fischer-Tropsch synthesis by choosing appropriate operating conditions for the SOEC. Based on this approach the co-electrolysis operating conditions were selected. The results of the stack durability tests (>4000 h) are shown and discussed.